REHABILITASI DAN PEMELIHARAAN SALURAN SEKUNDER PANJATAN DAERAH IRIGASI SAPON KABUPATEN KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - , KHRISTIN PUJIYANTI; , Devi Oktaviana Latif, S. T., M.eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Secondary channel is very important in the field of irrigation, which serves to distribute water from the primary to the tertiary canal channel. Rehabilitation of the channel is the usual activities if service life has reached the maximum number of channels. This study specifically addresses how the rehabilitation phase channel from the beginning to the end of the work. Besides evaluating the dimensions of the channel and know the obstacles encountered and solutions in handling. Strickler Research method used to calculate the dimensions of the channel. Based on existing data and analytical results it was concluded that the dimensions of the channel width of 0.9 meters to 0.85 meters for the channel and the channel height.